Two-phase mixed convection flow over a vertical stretching sheet with aligned magnetic field and newtonian heating - Nur Syamilah, Arifin (2019)
The phenomena of two-phase system (fluid and solid) can be found in many applications, for instance, the air or water pollution, blood flow in arteries, flows in rocket tubes, sedimentation and fluidized bed. The research on this two-phase system has been given considerable attention by many researchers due to its significant potential in investigating the fluid dynamics with the suspension of the solid particles. Instead of only focused on the fluid flow (one phase), this two-phase model examines the distributions of both fluid and solid particles. This implies that the single phase model of fluid flow problem is modified into the two-phase model by the additional of the element of interaction between the fluid and solid particles. Note that, the solid particle is assumed to be in the form of ash, soot and dust. In this thesis, the modified model is investigated theoretically by considering the dusty Newtonian fluid and dusty non-Newtonian fluid, in which the derivation for the particular proposed model have been formulated based on two-phase flow model. Specifically, the flow and heat transfer of both Newtonian and non-Newtonian (Casson, Williamson and Jeffrey) fluids are considered in the presence of dust particles. Besides, this thesis concerns on the influences of aligned magnetic field and mixed convection associated with the thermal boundary conditions of Newtonian heating (NH) where it passed along a vertical stretching sheet. Under these conditions, the single phase flow of Newtonian fluid without the dust particles is also given attention in order to study the characteristic of fluid flow independently before proceeding further with investigation for both fluid and dust particles. The governing equations of all proposed models in the form of partial differential equations are transformed into the ordinary differential equations by employing the suitable similarity transformation. The numerical computations for the obtained equations are then computed using the Keller-box method which is programmed in MATLAB software. The results are presented for the velocity and temperature distribution together with the skin friction coefficient and Nusselt number. Several physical parameters such as fluid-particle interaction, aligned angle, magnetic field, mixed convection, conjugate parameter for NH, Prandtl number, as well as the representative parameters for each fluid model are investigated in details. It is found that, the velocity and temperature behavior of all types of fluid are affected by the presence of dust particles, in which it has the tendency to decrease velocity and temperature distribution of fluid. Moreover, the aligned angle parameter is acknowledged as the controlling parameter, which can control the intensity of magnetic field. Meanwhile, the representative parameters for the fluid models concentrated in this thesis, which encompass of Casson, Williamson and ratio of relaxation to retardation times improved the temperature distribution of fluid as well as dust phase, whereas the reverse trend occurs for velocity distributions. Comparative results of all proposed models show that dusty Newtonian fluid has the highest distribution in the flow field in comparison to dusty non-Newtonian fluid. However, dusty Casson fluid has the higher heat transfer characteristic compared to dusty Williamson fluid and dusty Jeffrey fluid.